Possible high temperature superconducting transitions in disordered graphite obtained from room temperature deintercalated KC8. (5th January 2023) - Layek, Samar; Monteverde, Miguel; Garbarino, Gastón; Méasson, Marie-Aude; Sulpice, André; Bendiab, Nedjma; Rodière, Pierre; Cazali, Romain; Hadj-Azzem, Abdellali; Nassif, Vivian; Bourgault, Daniel; Gay, Frédéric; et al.
Abstract: Although progress with twisted graphene nano-devices is boosting the superconductivity that is the consequence of their Moiré flat electronic bands, the immense choice for future development is an obstacle for their optimisation. We report here that soft-chemistry deintercalation of KC 8 breaks down graphite stacking generating a strong disorder that includes stacking twists and variable local doping. We obtain a bulk graphite whose individual crystallites have different stackings with arbitrary twists and doping, scanning in the same sample a huge number of stacking configurations. We perform magnetisation measurements on batches with different synthesis conditions. The disorder weakens the huge diamagnetism of graphite, revealing several phase transitions. A tiny "ferromagnetic-like" magnetisation appears with Curie temperatures T 0 ∼ 450 K, that has to be subtracted from the measured magnetisation. Depending on sample synthesis, anomalies towards diamagnetic states appear at T c ∼ 110 K (3 samples), ∼ 240 K (4 samples), ∼ 320 K (2 samples). Electrical resistivity measurements yield anomalies for the T c ∼ 240 K transition, with one sample showing a 90% drop. We discuss the possibility that these (diamagnetic and resistive) anomalies could be due to superconductivity. As the amount of these phases is small by construction, fine-tuning of the process will be necessary to increase their fraction and select the desired phase. Graphical abstract: